2017
DOI: 10.5194/amt-10-825-2017
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous retrieval of water vapour, temperature and cirrus clouds properties from measurements of far infrared spectral radiance over the Antarctic Plateau

Abstract: Abstract. The possibility separating the contributions of the atmospheric state and ice clouds by using spectral infrared measurements is a fundamental step to quantifying the cloud effect in climate models. A simultaneous retrieval of cloud and atmospheric parameters from infrared wideband spectra will allow the disentanglement of the spectral interference between these variables. In this paper, we describe the development of a code for the simultaneous retrieval of atmospheric state and ice cloud parameters,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 55 publications
0
21
0
Order By: Relevance
“…Temperature and water vapour concentrations for each layer were obtained by interpolating the corresponding dropsonde measurements onto the 0.1 km vertical grid, with the exception of the layer closest to the aircraft which was prescribed by the onboard measurements. In the absence of direct measurements, concentrations of CO 2 and minor trace gases were obtained from a standard midlatitude winter (MLW) atmospheric profile (Anderson et al, 1986) and scaled to present-day concentrations using data from Mace Head (Dlugokencky et al, 2019). Ozone concentrations were obtained from co-located ERA-I data and interpolated to the required vertical resolution.…”
Section: Simulation Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…Temperature and water vapour concentrations for each layer were obtained by interpolating the corresponding dropsonde measurements onto the 0.1 km vertical grid, with the exception of the layer closest to the aircraft which was prescribed by the onboard measurements. In the absence of direct measurements, concentrations of CO 2 and minor trace gases were obtained from a standard midlatitude winter (MLW) atmospheric profile (Anderson et al, 1986) and scaled to present-day concentrations using data from Mace Head (Dlugokencky et al, 2019). Ozone concentrations were obtained from co-located ERA-I data and interpolated to the required vertical resolution.…”
Section: Simulation Methodologymentioning
confidence: 99%
“…Unsurprisingly, these showed excellent agreement with the observations in the MIR window from 820 to 960 cm −1 but large residuals were apparent in the FIR from 330 to 600 cm −1 . More recent work by Palchetti et al (2016) and di Natale et al (2017) has suggested that simulated and observed downwelling radiances at the surface can be reconciled within uncertainties across much of the FIR and MIR range if temperature, water vapour and cirrus properties are simultaneously retrieved from the observations. Maestri et al (2019) reported the first tentative retrievals of ice particle habit from downwelling FIR spectra obtained by REFIR-PAD over Antarctica in 2013, although they noted that large residuals in their retrievals did not permit clear identification of ice particle habit in most cases.…”
Section: Introductionmentioning
confidence: 99%
“…Data analyzed in the present work are collected at the Italian‐French research station of Concordia, located on the Antarctic Plateau at Dome C (75° 06 ′ S, 123° 23 ′ E) at 3.233 m a.s.l. Several scientific objectives are pursued by this experiment (Liuzzi et al, ; Rizzi et al, ; Di Natale et al, ). Among them, of our interest, is the study of clouds and the improvement of radiative transfer forward models and retrieval methodologies with particular attention devoted to the underexplored FIR region.…”
Section: Antarctic Campaign Setupmentioning
confidence: 99%
“…Between 400 and 600 cm −1 , several semitransparent FIR “dirty window” bands where water vapor absorption is moderate (Rathke et al, 2002) are useful for ice cloud property retrievals as they have sufficient sensitivity to ice cloud properties (Yang et al, 2003). Most previous studies focus on the sensitivity of ground‐based FIR measurements to ice cloud properties (Di Natale et al, 2017; Maestri et al, 2014; Mlynczak et al, 2016), and only a few studies investigate the corresponding sensitivity of upwelling FIR signals (Bantges et al, 2020; Cox et al, 2010). Libois and Blanchet (2017) demonstrate that synergistic measurements of upwelling MIR‐FIR radiation significantly reduce the uncertainty in ice cloud property retrievals.…”
Section: Introductionmentioning
confidence: 99%